Biotechnology for developing-country agriculture: problems and opportunities - Persley, Gabrielle Josephine (International Food Policy Research Institute, 1999)
Today, almost a billion people live in absolute poverty and suffer from chronic hunger. Seventy percent of these individuals are farmers—men, women, and children—who eke out a living from small plots of poor soils, mainly in tropical environments that are increasingly prone to drought, flood, bushfires, and hurricanes. Crop yields in these areas are stagnant and epidemics of pests and weeds often ruin crops. Livestock suffer from parasitic diseases, some of which also affect humans.